2003
DOI: 10.1179/joc.2003.15.6.563
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Pharmacokinetics and Theoretical Pharmacodynamics of Intravenous Levofloxacin in Intensive Care Unit Patients Treated with 500 mg b.i.d. for Ventilator-Associated Pneumonia

Abstract: This study assessed the urinary pharmacokinetics and theoretical pharmacodynamics of levofloxacin in ICU patients treated with 500 mg b.i.d. i.v. for ventilator associated pneumonia to evaluate if this high dosage regimen might ensure appropriate exposure in the treatment of severe UTIs in ICU patients. Nineteen patients (11M, 8F; age, 52 +/- 21 years; weight, 75 +/- 16 kg) presenting with normal renal function (estimated creatinine clearance, 1.83 +/- 0.61 ml/min/kg; diuresis, 1709 +/- 643ml / 24h) were asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…Fosfomycin is excreted in the active form in the urine via the kidneys and might achieve in vivo concentrations above the usual MIC against common uropathogens (9,10). The same studies demonstrated that serum susceptibility data overestimated the resistance of urinary isolates in the presence of high urine antibiotic levels (10,(31)(32)(33). Even though only the higher doses may be required to achieve the PTA for an MIC of 64 g/ml, fosfomycin becomes highly concentrated in the urine.…”
Section: Discussionmentioning
confidence: 77%
“…Fosfomycin is excreted in the active form in the urine via the kidneys and might achieve in vivo concentrations above the usual MIC against common uropathogens (9,10). The same studies demonstrated that serum susceptibility data overestimated the resistance of urinary isolates in the presence of high urine antibiotic levels (10,(31)(32)(33). Even though only the higher doses may be required to achieve the PTA for an MIC of 64 g/ml, fosfomycin becomes highly concentrated in the urine.…”
Section: Discussionmentioning
confidence: 77%
“…Even in complicated UTI the two dosages studied should be at the lower border. It has even been shown that a dosage regimen of levofloxacin 500 mg bid may ensure optimal exposure for the treatment of catheter-related and severe lower UTIs in intensive care patients [25].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with early-onset ventilator-associated pneumonia Pea et al [36] found a reduced area under the concentration-time curve (AUC) over the 12-hour dosage interval after the administration of parenteral levofloxacin 500 mg twice daily. The authors explained the reduction by a greater clearance of levofloxacin leading to a shorter elimination half-life.…”
Section: Pk/pd Parameters For Treatment Of Severe Utimentioning
confidence: 99%